Effect of NCOR1 Mutations on Immune Microenvironment and Efficacy of Immune Checkpoint Inhibitors in Patient with Bladder Cancer - Lin, Anqi; Qiu, Zhengang; Zhang, Jian; Luo, Peng (Frontiers in Immunology, 2021)
Immune checkpoint blockade (ICB) therapy has made significant progress in bladder cancer (BLCA). Multiple studies suggest that specific genetic mutations may serve as immune biomarkers of ICB therapy. Additionally, the NCOR1 gene is a new player in the field of immune tolerance and the development of immune cells. In the ICI-treated-cohort, NCOR1 mutations may be used as a biomarker to predict the prognosis of BLCA patients receiving ICIs. The overall survival(OS) of NCOR1-mutant(NCOR1-MT) was significantly longer than that of NCOR1-wild-type(NCOR1-WT) (P=0·031;HR(95%CI):0·25(0·12-0·52)). In the TCGA-BLCA-cohort, compared with NCOR1-WT, NCOR1-MT was associated with known predictors of ICB therapy efficacy, such as higher TMB, neoantigen load and the number of DNA-Damage-Repair pathway mutations. In addition, NCOR1-MT has highly infiltrating TILs, activated antitumor immunity, and a high expression of immune-related genes, suggesting that NCOR1 mutations may serve as a potential biomarker to guide ICB therapy in BLCA.